Effects of Milking Frequency of Dairy Goats on Milk Yield and Composition and on System Profitability - Martinez, Gabriela Marcela; Suarez, Victor Humberto; Alfaro, Emilio José; Alfaro, Rodolfo Jose (Juniper Publishers, 2022)
The effects of once (1X) vs twice (2X) daily milking frequency on milk yield and chemical composition of multiparous Saanen biotype goats were evaluated during the second third of lactation. Goats were assigned to one of two treatment groups, once daily milking at 0500 (1X, n=18) and twice daily milking at 0500 and 1700 (2X, n=18). Milk yield and composition were recorded weekly during 12wk. Differences in variables between groups were compared using an analysis of variance. Mean milk yield of X2 (2.5±?) was significantly (p<0.05) higher than that of X1 (2.09±?), representing an increase of 19.61%. Milk fat and protein content were also higher (p<0.05) in X2 (3.86 and 3.18%) than in X1 (3.13 and 2.99%). This study demonstrates a low to moderate increase in milk yield and quality under 2X during the second third of lactation in multiparous Saanen goats.